Inversão Geométrica Aplicada à Resolução dos Problemas de Apolônio - Sousa, Cristiano Benevides de (2014)
This work was developed with the aim of presenting a new approach within the Geometry, the Inversion. The Inversive Geometry is a non-Euclidean geometry that has several applications, mainly related to problems of tangency. This new Geometry is presented throughout this work in order to solve the ten problems of Apollonius. All constructions are carried out with the aid of a Dynamic Geometry software, Geogebra. Since the work is directed to teachers and students of basic education, then there is a proposed roadmap for the reader to participate in the construction of the solutions of these problems process, which will enable the development of creativity, logical thinking, reasoning and practice of geometric constructions.